Audit Quality dan Tax Avoidance dimediasi oleh Earning Management - Syarif M Helmi; Ahmad Kurniadi (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
This study aims to examine the influence of audit quality on tax avoidance, mediated by earnings management. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017–2020. The study employed a purposive sampling method, resulting in 113 companies meeting the criteria for analysis and processing using SPSS 25 software. The data analysis techniques used in this study include descriptive statistics, classical assumption tests, path analysis, hypothesis testing, simple linear regression analysis, and intervening (mediation) effect testing. The results of this study indicate that audit quality influences tax avoidance, audit quality influences earnings management, earnings management influences tax avoidance, and indirectly, audit quality through earnings management does not have an effect on tax avoidance.